PUBLIC INTELLIGENCE MINING AND USER INTENTION UNDERSTANDING BASED ON K-ANONYMITY - S.Kavitha Bharathi , K. Ramkumar , K.Srihariakash (International Journal of Advanced Science and Technology, 2020)
The quick improvement of Internet innovation, arrange clients and information are likewise quickly accumulating, which prompts different between client requirements and huge data. Subsequently, how to see client aims and give clients customized and exact data turns into a significant research theme; simultaneously, the Internet has gotten another critical wellspring of Public Intelligence, generally utilized in political, financial, military and different ﬁelds, individuals need to investigate another Internet-based open knowledge assortment and preparing innovation. In view of partial request contrast entail, Public Intelligence mining patterns is developed. Public Intelligence (PI) aimed at aggregating the collective work of independent researchers around the globe who wish to defend the public’s right to access information. Based on k-anonymity algorithm we can construct the same set of information results mining in the quick manner. In this paper moreover applies data mining quantifiable assessment development and checking advancement to the mining the user needs and Public Intelligence on the Internet; as showed by the authentic needs of customers, the extracting information relies upon data base estimations and examination